Experimental Versus Numerical Investigation into the Effects of Hoop Welding in Metallic Pressure Vessels with Spherical Caps - Jaber Mirzaei; GH Rahimi; Saleh Yazdani (International Journal of Advanced Design and Manufacturing Technology, 2012)
In this paper, an experimental and numerical investigation into the effect of the hoop welding in metallic pressure vessel is presented. In the experimental manufacturing, hoop welding was used to attach the cylindrical body of the vessel, and the effect of welding into stress and strain distribution is carried out. Experimental strains are obtained by using the strain gauges attached to predetermined places and stresses calculated by using Hook’s law in composite materials. The results of the two methods are compared with each other.